Effects of cyclooxygenase-2 gene silencing on the biological behavior of SKOV3 ovarian cancer cells - GUO, FENG-JUN (Mol Med Rep, 2015)
The aim of the present study was to investigate the effects of plasmid-mediated RNA interference targeting of cyclooxygenase-2 (COX-2) on the biological behaviors of SKOV3 human ovarian cancer cells and to analyze the function of COX-2 in carcinogenesis and development of ovarian cancer. A COX-2 small hairpin (sh)RNA sequence was designed and synthesized and pGPU6-COX-2-shRNA plasmids were constructed. The recombinant vector plasmids were stably transfected into SKOV3 cells. The mRNA and protein expression of COX-2 was subsequently analyzed by quantitative polymerase chain reaction and western blot analysis, respectively. MTT and colony formation assays were used to detect the cellular proliferation ability and flow cytometry was performed to detect phase changes in the cell cycle. Finally, a Transwell assay was used to detect cell invasion. The SKOV3 cells, transfected with recombinant vector plasmids, and control cells, were injected into nude mice and the tumor emergence time, volume and weight were measured. The impact of COX-2 gene silencing on the growth of xenograft tumors in nude mice was analyzed. Following transfection of the pGPU6-COX-2-shRNA plasmid, in vitro analyses indicated that the shRNA efficiently suppressed the mRNA and protein expression of COX-2. COX-2 gene silencing significantly inhibited the proliferation and invasion ability of SKOV3 cells, leading to cell cycle arrest in G1. The tumor formation time in the interference group was significantly prolonged, and the tumor volume and weight were significantly decreased, as compared with the control group. Plasmid-mediated shRNA was shown to effectively silence COX-2 expression in SKOV3 ovarian cancer cells. It was identified that COX-2 functioned in regulating proliferation, cell cycle and invasion of ovarian cancer cells. These findings provided a theoretical basis for determining the function of COX-2 in the development of ovarian cancer and suggested that COX-2 may be an effective target for gene therapy and clinical applications.